KUALITAS HIDUP KLIEN KANKER SERVIKS YANG MELAKUKAN KEMOTERAPI DI RUANG BOUGENVIL RSUD PROF. DR. MARGONO SOEKARJO - Suci Khasanah; Etika Dewi Cahyaningrum (Viva Medika, 2013)
The prevalence of cervical cancer is widely available in developing countries like Indonesia with a total incidence of 40-45 new cases per day. Cervical cancer usually affects women whoare already sexually active, especially who have many sexual partners and having sex at theage under 20 years old. Cervical cancer is the first cancer killer among other cancers in womenwith cervical cancer mortality by 20-25 cases per day. Therefore we need proper treatment toovercome. Chemotherapy is one of the management of cervical cancer with distant metastases andlocal or regional recurrence that does not respond to surgery or radiation therapy.Chemotherapy can cause side effects, both physically and psychologically for the client. One ofthe psychological effect is decreased quality of life. The purpose of this research is to describe the quality of life for clients who undergochemotherapy for cervical cancer based on age and stage of the cancer in the room BougenvilHospital Prof. Dr. Margono Soekarjo Purwokerto. This study uses quantitative and descriptive analytic design with cross sectional approach.Sampling using accidental sampling technique using a questionnaire which was distributed to23 respondents. Data were analyzed using univariate analysis followed bivariate analysis usingchi square. Keywords: quality of life, cervical cancer, chemotherapy